Impact of Leadership Style, Organizational Culture, and Work Motivation on Employee Performance - Hadyu, Rena Alfatih Dinul; Susanti, Anis (Manunggal Halim Jaya, 2026)
Employee performance plays a crucial role in ensuring the success of public service delivery at the village government level, particularly in response to increasing demands for professionalism and accountability. In public sector organizations, leadership style, organizational culture, and work motivation are considered key factors influencing employee performance. Therefore, this study aims to examine whether leadership style, organizational culture, and work motivation have significant effects on employee performance in village offices in Ajibarang Subdistrict. This research employs a quantitative approach using a causal research design. Data were collected through questionnaires distributed to village office employees selected using a random sampling technique. Multiple linear regression analysis was used to test the hypotheses, supported by classical assumption tests. The results indicate that leadership style has a significant positive effect on employee performance. Organizational culture and work motivation also have significant positive effects on employee performance. Simultaneously, leadership style, organizational culture, and work motivation significantly influence employee performance. These findings highlight the importance of strengthening effective leadership, fostering a supportive organizational culture, and enhancing employee motivation to achieve optimal performance and improve the quality of public services in village government institutions.